Nephroprotective effect and untargeted metabolomic analysis of celery extract against diethylene glycol induced nephrotoxicity in rats - Wijaya, Triyadi Hendra; Ekowati, Heny; Wasito, Hendri; Maryellen, Geeta; Silitonga, Tasya Melinda; Oktavian, Firdaus (Universa Medicina, 2025)
Background Diethylene glycol (DEG) is known for its nephrotoxic effects as a contaminant. Recent investigations suggest that celery extract potentially protects against DEG-induced renal toxicity, warranting an exploration of the non-targeted metabolomic profile of celery in renal tissue. This study aimed to determine celery nephroprotective effects and identify potential biomarkers using an untargeted metabolomic  celery profile in DEG-induced kidney injury in male rats. Methods An experimental study was conducted involving 24 male Wistar rats, randomized into control and three treatment groups receiving DEG at doses of 1, 3, and 5 g/BW for three days. After 14 days, all rats were sacrificed. For the celery nephroprotective and metabolomic study, 27 male rats were randomized into three groups:  control, DEG group at 3g/BW, and DEG-celery group (receiving celery extract 200mg/kg BW single dose for 6 days). After 14 days, blood was tested for creatinine level and untargeted metabolomic analysis using liquid chromatography-high resolution mass spectrometry. One-way ANOVA was used to analyze creatinine data. Results Diethylene glycol at doses of 1 and 3 g/kg BW caused mild renal damage, while 5 g/kg BW resulted in moderate damage. Creatinine levels in the normal, DEG-induced, and DEG-celery groups were 0.55 ± 0.14, 0.71±0.1, and 0.86± 0.17 mg/dL, respectively, but not statistically significantly different between groups (p>0.05). DEG lead tryptophan and phenylalanine levels increased 45-fold and 123-fold, respectively. Celery reduced levels of these metabolites 21-fold and 65-fold, respectively. Conclusion Diethylene glycol led to mild to moderate renal damage. Celery effectively diminished metabolite levels associated with renal damage, specifically tryptophan and phenylalanine.